Cleopatra on italian stages of the second half of XXth century (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2011)
Even if a large number of plays were written about Cleopatra from the 16th century on, they rarely were actually staged, with the only exception of the very difficult Shakespeare’s Antony and Cleopatra. This is quite the only play which has been staged in the 20th century Italian theaters as well, thanks to the effort of directors such as Renzo Ricci and Mario Missiroli. Only in recent years Cleopatra was protagonist of a new play, written by Giovanni Testori.
Keywords: cleopatra; renzo ricci; mario missironi; giovanni testori; drama